Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3141/2645-09
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Calculating Latency of GPS Probe Data

Abstract: Crowdsourced GPS probe data has been gaining popularity in recent years as a source for realtime traffic information. Efforts have been made to evaluate the quality of such data from different perspectives. A quality indicator of any traffic data source is latency that describes the punctuality of data, which is critical for real-time operations, emergency response, and traveler information systems. This paper offers a methodology for measuring the probe data latency, with respect to a selected reference sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 5 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…This paper uses the definition and implements the methodology given by Wang et al ( 7 ) to measure and analyze the latency of probe data. It includes data preparation, data filtering, interpolation, smoothing, and finally data shifting to calculate latency.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper uses the definition and implements the methodology given by Wang et al ( 7 ) to measure and analyze the latency of probe data. It includes data preparation, data filtering, interpolation, smoothing, and finally data shifting to calculate latency.…”
Section: Methodsmentioning
confidence: 99%
“…In their previous work (7), authors had observed that latency is not symmetric for each SRE, meaning that the probe data feed might reflect the reduction in the speed with less latency compared to the speed recovery. To revisit that observation, all SRE cases are examined and the percentage of cases that show higher latency in SP compared to RP are reported in table 4.…”
Section: Ffsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, these approaches are still characterized by high signal latency time during the broadcasting of corrections. Typically, this latency is in the range of seconds, which might be far from the requirements of the active solutions implemented on board of a vehicle [11][12].…”
mentioning
confidence: 99%